Mindfulness, psychological distress, and somatic symptoms among women engaged in sex work in China. Issue 3 (13th April 2022) - Tam, Cheuk Chi; Zhou, Yuejiao; Qiao, Shan; Li, Xiaoming; Shen, Zhiyong
Abstract: Women engaged in sex work (WSW) in China encounter numerous disadvantages (e.g., exposure to violence) and have substantial risk for psychological distress and somatic symptoms. Intervention literature has attended to mindfulness, which is a protective factor for psychological outcomes, and its influences can further improve physical health. However, mindfulness has not been well studied in WSW. We aimed to examine the association among mindfulness, psychological distress, and somatic symptoms among Chinese WSW. Data were collected from 410 WSW in Guangxi, China, using an anonymous, self‐administered survey evaluating demographics, mindfulness, psychological distress (i.e., depression, loneliness, and perceived stress), and somatic symptoms (i.e., pain, cardiopulmonary, and gastrointestinal/fatigue symptoms). Structural equation modeling was utilized for data analyses. Mindfulness was negatively associated with psychological distress and somatic symptoms. Psychological distress was positively associated with somatic symptoms. Psychological distress mediated the association between mindfulness and somatic symptoms. Mindfulness appears to be a protective factor for psychological distress among WSW, and such an effect is further influential to their somatic symptoms. Our findings add to the growing literature on mindfulness, suggesting that mindfulness‐based interventions could be beneficial for WSW. Future research should explore other cognitive factors underlying the psychosomatic mechanism of mindfulness.